Exploring Mean Reversion Dynamics in Financial Markets: Insights from Hurst Exponent Analysis - Hasan, Shifa; Ghosh, Renu (The Indonesian Capital Market Review, 2024)
The current study investigates mean reversion and the speed of mean reversion within financial mar- kets at BSE 200 and NSE Nifty 200 for a data set of 20 years (2004–2024). It employs a variety of techniques, including traditional tests like the Augmented Dickey-Fuller (ADF) and Philips-Perron (PP) tests, as well as long-term dependency analysis using the Hurst exponent. The Ornstein-Uhlen- beck process facilitated the speed of mean reversion. Empirical data demonstrates that mean rever- sion processes exhibit Hurst exponent values less than 0.5, suggesting mean reverting behaviour. This signifies the importance of adopting long-term perspectives in decision-making and trading strate- gies for market participants. Additionally, the half-life values for BSE 200 is 52 days whereas it is 51 days for Nifty 200. The research highlights the significance of integrating mean reversion analysis into investment strategies, showcasing its potential for capitalizing on pricing inefficiencies, mitigat- ing downside risks, and enhancing long-term performance.